Multifactor model of risk and return through enterprise risk management framework - Lai, Fong Woon; A. Samad, M. Fazilah; Azizan, Noor Azlinna (2011)
This paper presents a multifactor risk pricing model which conceptualizes a strategic risk premium framework in which the value enhancing dimension of managing firm-specific risks is factored into the reduction of the firm’s risk premium. The model’s concept of managing these firm-specific risks is embodied in an enterprise risk management (ERM) implementation framework. ERM is defined as the process of identifying and analyzing risk from a holistic and company-wide perspective. Findings of this study have provided a perspective on a productive management of firm-specific risk. They vindicate the efficacy of ERM in creating value for the firms. It lends reference to enterprises for adaptation of their own internal risk management modeling. The test results have implied that Malaysian listed companies are poised to benefit from a favorable credit profile rating if they put in place an effective ERM program as this will lead to lower risk premium, hence reducing their cost of capital.